Hypermedia Based Science Project Teaching Materials for First Grade Vocational High School - Naimah, Auliya; Situmorang, Robinson; Kusumawardani, Dwi (Journal of Education Reseach and Evaluation, 2025)
Science learning should develop critical thinking, collaborative, and problem-solving skills, but it is often still delivered conventionally, so it has not optimally aroused students' interest in learning. The purpose of this study is to develop hypermedia-based learning materials for Natural and Social Sciences (IPAS) projects in vocational high schools for grade X. This study uses the Research and Development (R&D) method using the Dick and Carey development model and the Lee & Owens model. The subjects of this study are material experts, instructional design experts, and learning media experts. The trial subjects are 30 grade X students. The methods used to collect data are observation, interviews, questionnaires, and tests. The instruments used to collect data are questionnaires and tests. Data analysis techniques use qualitative and quantitative descriptive analysis. The media effectiveness test is carried out by calculating the N-Gain value. The results of this study indicate that the developed learning materials effectively increase student engagement and understanding of the learning materials. Validity tests conducted by material, media, and language experts indicate that these learning materials are in the "very valid" category and suitable for use. Thus, hypermedia-based learning materials are effective in improving the quality of learning. The implications of this research indicate that the development of hypermedia-based science and science project teaching materials can effectively improve the quality of learning in vocational schools, especially in accommodating the needs of students who are more active, visual, and accustomed to digital technology.